Gas chromatography – Mass spectrometry (GC-MS) profiling reveals newly described bioactive compounds in Citrullus colocynthis (L.) seeds oil extracts - Faten Hameed Thamer; Noah Thamer (Heliyon, 2023)
Citrullus colocynthis (L.) (C. colocynthis), commonly known as Handal in Yemen and other Arabic countries, is a plant with a wide range of pharmacological properties. These properties are attributed to secondary metabolites, known as phytochemicals, present in the plant. In this study, the seed of C. colocynthis were extracted using dichloromethane, and the resulting oil extract was screened to identify active phytoconstituents using gas chromatography – Mass spectrometry (GC-MS). The gas chromatography – Mass spectrometry is used to identification of the phytoconstituents and the spectrum of unknown compounds were compared with the compounds stored in the National Institute of Standards and Technology Mass Spectral database (NIST) and WILEY library of GC-MS. A total of fifty five compounds appeared in GC-MS chromatogram, twenty-four major bioactive compounds were identified in the present study. The major components of the oil extract were found to be carotenes, phenols, esters, and steroids. From the GC-MS chromatogram of dichloromethane seeds oil extract, some of the identified components possess pharmacological actions as per information available in the literature. One of the major component identified in the C. colocynthis seed oil extract was isooctylphthalate (58%), which exhibit strong antimicrobials effect. Therefore, C. colocynthis is considered to be a natural source of isooctylphthalate. From the results, this study is the first to report the presence of various bioactive components of phytopharmaceutical importance in C. colocynthis.